The sowing date of winter durum wheat - A. S. Popov (Зерновое хозяйство России)
Winter durum wheat is one of the most important crops. This grain crop forms the grain from which high-quality pasta and groats are obtained. The insufficient knowledge of the elements of cultivation technology of this grain crop is one of the factors that limits its widespread use. The sowing date is one of the main elements of cultivation technology of winter durum wheat, which determines the duration and conditions of vegetation, which its productivity depends on. The study was carried out at the FSBSI “Agricultural Research Center “Donskoy” in 2013–2018 in the field crop rotation of the laboratory of grain crop cultivation technologies. There were studied four sowing dates, September 10, 20, 30 and October 10 according to three forecrops (weedfree fallow, peas, sunflower). The total area in the trials was 55 m2, and the accounting area was 41.25 m2, fourfold repetitions. The arrangement of variants in the repetitions was systematic and sequential. The trial was laid down and carried out in accordance with Dospekhov’s methodology of a field trial (1985). As a result of the conducted study, it was determined that the minimum period from sowing date to winter durum wheat sprouting was in the variant with weedfree fallow (from 21 to 27 days) maximal period was in the variant with sunflower (from 27 to 37 days). From the germination period to the finish of autumn vegetation of winter durum wheat (from the early sowing date (September 10) to the late sowing date (October 10)), the vegetation period of the plants decreases, their provision with positive and active temperatures and moisture increases depending on the forecrop. The largest productivity of winter durum wheat was obtained due to weedfree fallow (from 5.74 to 6.44 t/ha), and the smallest productivity of winter durum wheat was obtained when sown after sunflower (from 4.61 to 5.09 t/ha). For all forecrops, the largest yields of winter durum wheat are formed when sowing from September 10 to September 30, which proved to be optimal for this grain crop.